(untitled) (Al-Academy, 2017)
Playing is the only common language among children in every place and time, to the fact that what distinguishes the children is their quest to play and fun way innate, not acquired, which is expressed with the child really is one of the rights. And play a key entrance to the growth of the child mentally, intellectually and cognitively and not for the child emotionally and socially just. In the play the child begins to identify and classify objects and learn concepts and circulate among themselves on a linguistic basis. Activity here and play a major role in leading the linguistic development of the child in the composition has the communication skills. The Games (especially intellectual ones) Whatever the cause of the development of children’s skills and education, which is a fertile source of learning resources and a factor of mental development of the child factors, and this fact has shown a range of studies carried out by a number of researchers in the field of children’s toys, including (Jean Piaget and Frederick Frobel and Torrance), who stressed the critical importance of play in solving problems and getting the knowledge that knowledge abstract that may come to the children through the narrative, education, Playing gives the kids a chance to come to grips inform them and to discover and develop themselves and discover others and develop personal relationships with those around them and gives them a chance tradition the others.